2014
DOI: 10.1111/cch.12223
|View full text |Cite
|
Sign up to set email alerts
|

Peer support for parents of disabled children part 1: perceived outcomes of a one‐to‐one service, a qualitative study

Abstract: Background: Parents of disabled children are encouraged to seek peer support. Delivering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 33 publications
5
48
0
Order By: Relevance
“…The theme of support was evident although it ranged from support within the couple to the wider family, to seeking out and accessing support from other parents who were going through similar experiences. This provides parents with a shared social identity and enables them to learn from the experiences of others (Shilling et al 2013), and use of peer support groups has been found to benefit parents across a range of chronic health conditions (Kerr and McIntosh 2000;Shilling et al 2015;Tong et al 2008), both online and in person (Bray et al 2017). An emergent theme was the use of faith and spirituality to cope with unknown or difficult experiences, which has been shown to support parent coping (Raingruber and Milstein 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The theme of support was evident although it ranged from support within the couple to the wider family, to seeking out and accessing support from other parents who were going through similar experiences. This provides parents with a shared social identity and enables them to learn from the experiences of others (Shilling et al 2013), and use of peer support groups has been found to benefit parents across a range of chronic health conditions (Kerr and McIntosh 2000;Shilling et al 2015;Tong et al 2008), both online and in person (Bray et al 2017). An emergent theme was the use of faith and spirituality to cope with unknown or difficult experiences, which has been shown to support parent coping (Raingruber and Milstein 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It also highlights the potential importance of local parent advocacy groups, both as mechanisms for support and sources of information, as well as their core role in facilitating service user participation. Previous authors (Goodley & Tregaskis, 2006;Jackson, 2008;Shilling, Bailey, Logan, & Morris, 2014) also report the importance parents place on talking to other parents in the same situation as themselves in order to share experiences and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The patient and public involvement in the design and conduct of this research is described in more detail in the related paper (Shilling et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…In the first of this pair of papers we described the perceived outcomes of a one‐to‐one peer support service for parents of disabled children (Shilling et al . ). We reported, as have others (Ainbinder et al .…”
Section: Introductionmentioning
confidence: 97%